Phase difference of arrival range estimation for OFDM signal - Wang, Yiyi (Nanyang Technological University, 2023)
Location information has become essential in information technology. Due to the blocking of buildings and other factors, the mature and stable Global Positioning System (GPS) is not applicable in the indoor environment. So, accurate indoor locating has become an essential technology. Phase Difference of Arrival (PDOA) ranging is one of the indoor positioning technologies. Because the carrier phase is highly correlated with the signal’s time of flight (TOF), the distance calculation method based on the carrier phase can theoretically achieve higher accuracy.